IT Security Audit Based on CISSP PMBOK Framework - Arionadi, Kheri; Dharma, Suta Adya; Indra Partha, Cok Gede (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December)
XYZ International School redesign their IT System and Infrastructure to meet their target in implementing ICT based learning process. The implementation of new system and infrastructure have good impact in speed and accuracy of learning process but not yet evaluate in term of security matters. IT security audit perform to fulfill the evaluation need for security implemented in XYZ International School.  Audit perform based on CISSP common body of knowledge from (ISC) 2 and concentrate in Access Control area. Result show that security concern already implemented and have a good standard in certain area like identification, authentication, authorization and implementation, but still need improvement in accountability and monitoring area